The protection of relationship in adoption in particular cases: side notes of the sentence of the Constitutional Court n. 79/2022 (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
The paper aims to examine the most relevant aspects of the decision no. 79 of 11 February in which the Italian Constitutional Court declared illegitimate – with reference to articles 3, 31 and 117, first paragraph, of the Constitution, in relation to article 8 of the ECHR – article 55 of law n. 184 of 1983, where it required the rules laid down by art. 300, second paragraph, of the Civil Code for the adoption of adults to be applied to the adoption in particular cases of minors.
Keywords: Relationship; adoption; filiation; family; identity